Pengaruh Status Sosial Ekonomi dan Sikap Love Of Money Terhadap Persepsi Etika Mahasiswa Akuntansi Mengenai Tax Evasion Dengan Religiusitas Sebagai Variabel Moderasi - Rizkiyatul Komariyah; Nur Diana; Irma Hidayati (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the effect of socioeconomic status and love of money attitudes on ethical perceptions of accounting students regarding tax evasion with religiosity as a moderating variable. This research used a quantitative research type with the research population being students of the Faculty of Economics and Business, Islamic University of Malang, class of 2019 who were active and had taken taxation and business ethics courses. In this study a sampling technique was used which was determined based on purposive sampling using the Raosoft sample size calculator. The type of data used is primary data and data collection is done by distributing questionnaires. The data analysis method used in this study is Moderated Regression Analysis (MRA). The results of this study indicate that the variables of socioeconomic status, love of money attitude, religiosity, interaction of religiosity with socioeconomic status and interaction of religiosity with love of money attitude simultaneously influence the perceptions of accounting students regarding tax evasion. The variables of socioeconomic status and religiosity have a positive effect on accounting students' perceptions of tax evasion, while the attitude of love of money has no effect on accounting students' perceptions of tax evasion. The religiosity variable moderates the relationship between the socioeconomic status variable and the ethical perceptions of accounting students regarding tax evasion, while the religiosity variable does not moderate the relationship between the love of money attitude variable and the ethical perceptions of accounting students regarding tax evasion.Keywords: Love of money, tax evasion, religiusitas, moderated regression analysis.